Bioadsorbents using malt bagasse from brewery waste - Layza Lima Xavier, Rayssa; David Aragão de Oliveira, Antônio; Henrique Santiago de Lima, Venicius; Claudia Rodrigues dos Santos, Regina; Batista Vieira, Rômulo (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
The textile industry produces large volumes of effluents containing polluting chemical substances, such as dyes. Treating these contaminants is essential to minimize their socio-environmental impacts. [1]. A promising alternative is the use of agro-industrial waste, such as malt bagasse, which is abundant and inexpensive, as a bioadsorbent to remove dyes and heavy metals. [2] Thus, the goal of this work is to explore the potential of malt bagasse on methylene blue adsorption. The pristine, acid-modified (HCl, HNO3, H2SO4, and H3PO4) and activated carbon pyrolyzed at different temperature (500, 600, 700, and 800 °C) from malt bagasse were studied. These bioadsorbents were characterized by X-ray diffraction, indicating the presence of diffraction peaks at 16.4, 21.7° characteristics of lignocellulosic biomass (cellulose I), Fig. 1A (i). [3]. After the acid treatment, Fig. 1 (ii-v), there was no long-distance change in biomass structure. For activated carbons, Fig. 1A (ii-v), the cellulose I peak disappeared, suggesting a destruction of the lignocellulosic chains from malt bagasse; the presence of a diffraction peak at ~24° is consistent of a carbon amorphous arrangement. [1]. Just in CM@800, Fig. 1B (v), there was the appearance of peaks at 22 and 30° characteristics of inorganic minerals. The performance of bioadsorbents were evaluated by methylene blue adsorption at different concentrations (10–200 mg∙L-1 ), Fig. 1C. A highlight for MC@800, which removed 100% of methylene blue in all concentration studied. Meanwhile, the MB@HNO3 removed 100% of methylene blue in 50 and 100 mg∙L -1 concentrations. These bioadsorbents were submitted to the adsorption kinetics (180 min). Again, both adsorbents removed 100% of the methylene blue after 15 min, 200 mg∙L-1 for CM@800 and 100 mg∙L-1 MB@HNO3, respectively. According to the adsorption isotherms (not shown here), the CM@800 presented a characteristic kinetic profile of physisorption and the MB@HNO3, it displayed a chemisorption profile, respectively. This difference may be attributed to the oxidation of the malt surface (hydroxyl groups) in MB@HNO3, resulting in a stronger interaction with the methylene blue when compared to MC@800 bioadsorbent.